Prevalence and correlates of mental and neurodevelopmental symptoms and disorders among deaf children and adolescents: a systematic review protocol. Issue 10 (29th October 2020) - Swanepoel, Brandon; Swartz, Leslie; Gericke, Renate; Mall, Sumaya
Abstract : Introduction: Little is known of the prevalence and correlates of mental and neurodevelopmental symptoms and disorders among deaf children and adolescents. Research suggests that this is a vulnerable population group at high risk of these disorders. However, little is known of correlates of prevalence estimates of these mental disorders and it seems that heterogeneous tools have been used to derive these estimates. Given the heterogeneity of studies measuring the prevalence and correlates of mental and neurodevelopmental symptoms and disorders among deaf children and adolescents, we seek to systematically examine and synthesise observational epidemiological evidence in this area to articulate a more detailed account of these symptoms and disorders and their correlates among this population group. Methods and analysis: We will conduct a systematic search of the following electronic databases to identify published observational epidemiological studies examining the prevalence and correlates of mental and neurodevelopmental symptoms and disorders among deaf children and adolescents: EBSCOhost, ERIC, PsycARTICLES, PsycINFO, PubMED, ScienceDirect, SCOPUS and Web of Science. As research in this area is limited, eight databases have been included to widen our search to include as many articles as possible. The search terms will be related to mental and neurodevelopmental symptoms and disorders as well as deaf children and adolescents. Two reviewers will review and extract data from each article independently and, where relevant, discuss differences to reach consensus. Additionally, the reviewers will assess overall study quality and risk of bias using a quality appraisal scale. Findings from studies will be synthesised to produce a quantitative review that summarises existing evidence on mental and neurodevelopmental symptoms and disorders among deaf children and adolescents and their correlates. The publication date of studies will not be restricted so that as much data as possible that fit our inclusion criteria can be sourced. We will conduct our searches between August 2020 and March 2021. Ethics and dissemination: This systematic review will use publicly available data and therefore does not require a direct ethical review. The protocol was however submitted for ethics waiver clearance with Stellenbosch University Health Research Ethics Committee. The protocol will be disseminated in a peer-reviewed journal. The review protocol was registered with the PROSPERO International Prospective Register of systematic reviews (http://www.crd.york.ac.uk/PROSPERO ). PROSPERO registration number: CRD42020189403.